Risk/reward decision-making in schizophrenia: a preliminary examination of the influence of tobacco smoking and relationship to Wisconsin Card Sorting Task performance. - Yip, S; Sacco, K; George, T; Potenza, M (2009)
BACKGROUND: Individuals with schizophrenia show deficits in cognitive functioning, as evidenced by deficits on neurocognitive tasks such as the Wisconsin Card Sorting Task (WCST). Studies of risk/reward decision-making in individuals with schizophrenia have yielded mixed results, and few studies have examined systematically the relationship between these domains and their relationship with clinical factors. METHOD: Thirty-two smokers with schizophrenia, ten non-smokers with schizophrenia, nine non-psychiatric non-smokers and ten non-psychiatric smokers were administered computerized versions of the Iowa Gambling Task (IGT) and the WCST. Smokers were allowed to smoke adlibitum during designated breaks in order to prevent deprivation. RESULTS: Subjects with schizophrenia performed significantly worse than non-psychiatric controls on both the IGT and the WCST, and performance on these tasks was significantly correlated across subject groups. Among women with schizophrenia, smokers performed significantly better than non-smokers on the IGT. CONCLUSIONS: Individuals with schizophrenia perform worse than controls on the IGT, suggesting impairments in risk/reward decision-making. Correlations between IGT and WCST performance suggest a shared element underlying task performance, such as a deficit in set-shifting or perseverance. Further research is needed to establish the relationship between cigarette smoking and IGT performance in schizophrenia.